cum se rezolva? (-3)la 0 +(-3) la 42 ori (-3la 23):81 la 16
Răspunsuri la întrebare
Răspuns de
1
emanuelasimon:
va multumes
Răspuns de
1
(-3)⁰ +(-3)⁴² × (-3²³):81¹⁶ =
=1 +3⁴² ×(-3²³):(3⁴)¹⁶ =
=1 +3⁴² ×[-(3)²³]:3⁶⁴ =
=1 +3⁴² ×[-(3)⁻⁴¹] =
=1 +3⁴² ×[-(3)⁻⁴¹ ]=
=1-3=-2
=1 +3⁴² ×(-3²³):(3⁴)¹⁶ =
=1 +3⁴² ×[-(3)²³]:3⁶⁴ =
=1 +3⁴² ×[-(3)⁻⁴¹] =
=1 +3⁴² ×[-(3)⁻⁴¹ ]=
=1-3=-2
Alte întrebări interesante
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă